The Implementation of Text-Based Approach Within The K-13 Curriculum In Junior High School - Rahmawati, Euis; Vadilla, Nur; Hairani, Zahra; Hasibuan, Kalayo (Lembaga Riset dan Inovasi Almatani, 2024)
The teaching and learning process in junior high school for English learners is student- centred and focuses on oral and written texts. Texts play an important role in English language teaching. Qualitative research has been conducted to examine the implementation of the 2013 Curriculum in English language learning. This study specifically explores the application of a Text-Based Approach in the K-13 curriculum in junior high schools. The Text- Based Approach is a learning method that prioritizes the use of literary texts for foreign language teaching. The purpose of this study is to assess the effectiveness of the Text-Based Approach in Junior High School and identify the factors that affect its implementation. To achieve this, a literature review methodology has been used to analyse previous research and theoretical frameworks related to the Text-Based Approach and the K-13 curriculum. The findings of this study are expected to contribute to the development of effective language teaching strategies and provide insights for educators and policymakers on how to improve the implementation of Text-Based Approaches in the K-13 curriculum in junior high schools. The findings of this study are expected to contribute to the development of effective language teaching strategies and provide insights for educators and policymakers on how to improve the implementation of Text-Based Approaches in the K-13 curriculum in middle schools.